Trifarotene in the Treatment of Acne Vulgaris: Current Evidence and Place in Clinical Practice - Sowińska, Joanna; Paluszkiewicz, Natalia; Bryg, Sandra; Cieślak, Aleksandra; Demkow, Sara; Leżańska, Zofia; Kwiatkowski, Mateusz; Marcinkowska, Katarzyna; Siemińska, Karolina; Pałyga, Emil (Journal of Education, Health and Sport, 2026)
Background: Acne vulgaris is a highly prevalent chronic inflammatory skin disease that significantly affects quality of life and psychological well-being. Topical retinoids remain a cornerstone of acne therapy due to their comedolytic and anti-inflammatory properties. Trifarotene, a selective retinoic acid receptor-γ agonist, is a recently developed fourth-generation retinoid introduced for the treatment of both facial and truncal acne. Aim: This review aims to summarize current evidence on the pharmacology, clinical efficacy, safety, and role of trifarotene in the management of acne vulgaris. Materials and Methods: A narrative literature review was conducted using PubMed and Embase, including clinical trials, meta-analyses, case reports, systematic reviews, post-marketing studies, and international treatment guidelines published up to 2026. Results: Randomized controlled trials demonstrate that trifarotene effectively reduces both inflammatory and non-inflammatory lesions on the face and trunk, with a generally favorable safety and tolerability profile, predominantly characterized by mild, localized adverse reactions. Long-term data support sustained efficacy and improvement in quality of life. However, comparative evidence, including network meta-analyses and tolerability studies, suggests that trifarotene may be less effective, associated with higher rates of treatment discontinuation, and exhibit a greater propensity for local irritation compared with other topical retinoids. Emerging evidence, including a case report, indicates potential benefit in combination therapy, particularly in treatment-resistant acne. Conclusions: Trifarotene is an effective and generally well-tolerated treatment for acne vulgaris, demonstrating efficacy in both facial and truncal acne. However, its precise role in clinical practice remains to be established, given the lack of clear superiority over existing therapies and its higher cost.